A comparative study of electronic cigarette vapor extracts on airway-related cell lines in vitro. (23rd February 2017) - Leslie, Laura J.; Vasanthi Bathrinarayanan, Pranav; Jackson, Pamela; Mabiala Ma Muanda, Justin A.; Pallett, Ross; Stillman, Christopher J. P.; Marshall, Lindsay J.
Abstract: The use of electronic cigarettes (ECs) is rapidly increasing worldwide; however, scientific evidence regarding EC cytotoxicity is limited. The aim of this study was to evaluate the acute cytotoxicity of EC vapor extract (ECE) on airway-related cells in vitro . Cigarette smoke extract (CSE), vapor extract of fifteen brands/flavors of ECs and the extract from the E-vehicle (propylene glycol and glycerin) was collected. Extracts, in concentrations of 100–12.5%, were added to human bronchial epithelial (BEAS-2B, IB3-1 and C38), fibroblast (Wi-38) and macrophage (J774 and THP-1) cell lines. Viability was assessed after 24 h using a standard XTT assay. Viability of <70% of control (no extract) was considered cytotoxic according to UNI EN ISO 10993-5 standards. CSE displayed a concentration-dependent influence on cell viability across all four cell lines with 100% producing the most toxic effect, therefore validating the model and indicating higher cytotoxicity than in ECEs. ECEs did reduce viability although this was not correlated with nicotine content or the E-vehicle. However, several flavors proved cytotoxic, with variation between different brands and cell lines. These data indicate that not all ECs are the same and that use of a particular flavor or brand may have differing effects. The cell line used is also an important factor. More research is crucial to ascertain the health effects of different ECs before they can be accepted as a safe alternative to tobacco cigarettes.